2016
DOI: 10.1021/acs.jafc.5b05861
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Metabolite Profiling of Extreme Southern Pinot noir Wines: Effects of Vintage, Barrel Maturation, and Fermentation Dominate over Vineyard Site and Clone Selection

Abstract: Wine is an extremely complex beverage that contains a multitude of volatile and nonvolatile compounds. This study investiged the effect of vineyard site and grapevine clone on the volatile profiles of commercially produced Pinot noir wines from central Otago, New Zealand. Volatile metabolites in Pinot noir wines produced from five grapevine clones grown on six vineyard sites in close proximity, over two consecutive vintages, were surveyed using gas chromatography-mass spectrometry (GC-MS). The raw GC-MS data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…The wines from high typicity sites are usually described as being higher in complexity, aroma and flavour, compared to wines from low typicity sites. The vineyard sites sampled have previously been described in detail . In short, the vineyard sites were located within an area of 13 km 2 (Central Otago, NZ).…”
Section: Methodsmentioning
confidence: 54%
See 4 more Smart Citations
“…The wines from high typicity sites are usually described as being higher in complexity, aroma and flavour, compared to wines from low typicity sites. The vineyard sites sampled have previously been described in detail . In short, the vineyard sites were located within an area of 13 km 2 (Central Otago, NZ).…”
Section: Methodsmentioning
confidence: 54%
“…A similar pattern was observed from the analysis of PB samples by SPE‐GC–MS, as previously reported . It was suggested that wines from the site BR had the potential to express high site‐typicity in their wines (as confirmed by subsequent discussions with the winemaker).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations